Komposisi Floristik dan Struktur Hutan di Pulau Natuna Besar, Kepulaun Natuna - Mirmanto, Edi (JURNAL BIOLOGI INDONESIA, 2014)
Ecological study has been conducted in the forest area of Natuna Island to reveal the structure and composition oftree species. In the 10 plots of 20 x 40 m each, there were 141 species of trees, with a density of 504 trees / ha and12.35 m2/ha of basal area, which was distributed in three forest types. Myrtaceae was the most common family,followed by Euphorbiaceae and Dipterocarpaceae. On the other hand Arthrophyllum javanicum recorded as themost common species together with Syzygium aemum and Ilex pleiobrachiata. The existence of each of the common speciesvaries in each forest type that shows there was a correlation between the condition of the habitat and the presence ofspecies.Keywords: floristic composition, structure, the Natuna Besar, Riau